A battery anode material of Sb-doped SnO2 and a preparation method thereof
Patent Information
- Application Number
- CN202311640792.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-12-01
AI Technical Summary
The existing graphite anode material for lithium-ion batteries has a low capacity, which is difficult to meet the development needs of high energy density batteries. In addition, the existing SnO2 anode material requires a binder to be attached to the current collector, which poses a risk of loss of mass energy density and shedding.
Sn-Sb intermediate layer was prepared on current collector by electrodeposition, oxidized to SnO2-Sb by thermal treatment, and formed into three-dimensional nanosheet structure in hydrothermal reaction. Sb-doped SnO2 anode material was prepared by using alkyl quaternary ammonium salt surfactant to provide nitrogen doping sites, thus avoiding the use of binder.
It improves the conductivity and lithium-ion transport capacity of the electrode, reduces the interface resistance, enhances the stability and mass energy density of the battery structure, inhibits lithium dendrite growth, and extends battery life.
Smart Images

Figure BDA0004584406240000071 
Figure BDA0004584406240000072 
Figure BDA0004584406240000151
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a battery anode material doped with Sb and SnO2 and its preparation method. Background Technology
[0002] Lithium-ion batteries possess characteristics such as high voltage, high energy density, environmental friendliness, rechargeability, and long lifespan, making them widely used in mobile phones, small digital devices, electric vehicles, and other fields. They are currently a key research focus in the global new energy research field. At present, graphite is the primary anode material for lithium-ion batteries, but its relatively low capacity (372 mAh·g) is a concern. -1 It is difficult to meet the development needs of high energy density batteries.
[0003] The theoretical capacity of SnO2 metal oxide as a negative electrode material for lithium-ion batteries is 782 mAh·g. -1 SnO2 has a capacity far exceeding that of graphite, and its natural reserves are relatively abundant, inexpensive, and easy to prepare, making it a very promising anode material. Currently, most methods for preparing SnO2 anode materials are chemical methods. These methods are relatively simple, have low synthesis costs, and are suitable for large-scale production. However, the prepared anode material needs to be attached to the current collector using a binder, which consumes a certain amount of mass energy density, and there is a risk of the anode material detaching. Summary of the Invention
[0004] In view of this, the main objective of the present invention is to provide a battery anode material doped with Sb and SnO2 and a method for preparing the same, which can directly prepare the Sb-doped SnO2 anode material on the current collector without the use of a binder.
[0005] To achieve the above-mentioned objective, the first aspect of this invention provides a method for preparing an Sb-doped SnO2 battery anode material, comprising the following steps:
[0006] S1. Using the negative electrode current collector of the battery as the cathode, Sn-Sb intermediate layer is obtained by electrodeposition on the surface of the current collector.
[0007] S2. Heat-treat the current collector with the Sn-Sb intermediate layer on the surface to oxidize the Sn-Sb layer to SnO2-Sb;
[0008] S3. The current collector treated in step S2 is placed in a precursor solution containing an alkyl quaternary ammonium salt surfactant for hydrothermal reaction to obtain the electrode sheet.
[0009] S4. Anneal the electrode obtained in step S3 to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface.
[0010] Further, the electrodeposition system in step S1 includes: using an inert electrode as the anode, and the components of the deposition solution include additives, tin salts, antimony salts, and solvents; preferably, the additives include one or more of tartaric acid, sodium pyrophosphate decahydrate, and gelatin, the tin salt is stannous chloride dihydrate, the antimony salt is antimony trichloride, and the solvent is water;
[0011] More preferably, the composition of the sedimentation solution includes: 5-10 g·L⁻¹ -1 Tartaric acid, 100-120 g·L -1 Sodium pyrophosphate decahydrate, 20–40 g·L -1 Stannous chloride dihydrate, 3–6 g·L -1 Antimony trichloride, 0.5–1 g·L -1 Gelatin and water; more preferably, the composition of the sediment is 7-8 g / L. -1 Tartaric acid, 110-115 g·L -1 Sodium pyrophosphate decahydrate, 28–32 g·L -1 Stannous chloride dihydrate, 4-5 g·L -1 Antimony trichloride, 0.7–0.8 g·L -1 Gelatin and water.
[0012] Furthermore, in step S1, the electrodeposition method is direct current electrodeposition or pulsed electrodeposition, and the average current density is set to 10–30 mA·cm⁻¹. -2 The deposition time is 5–15 min; preferably, the average current density is 18–22 mA·cm⁻¹. -2 The deposition time is 8–12 minutes.
[0013] Furthermore, in step S2, the heat treatment temperature is 450–550°C, and the holding time is 20–60 min. Preferably, the heat treatment is carried out in an air environment.
[0014] Further, in step S3, the precursor solution includes an alkyl quaternary ammonium salt surfactant, a tin salt, an antimony salt, an alkaline solution, and a solvent; the alkyl quaternary ammonium salt surfactant is selected from one or more of hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, and dodecyldimethylammonium bromide, preferably hexadecyltrimethylammonium bromide (C 16 H 33 (CH3)3NBr, CTAB); the tin salt is anhydrous stannous chloride, the antimony salt is antimony trichloride, and the alkaline solution is sodium hydroxide or potassium hydroxide;
[0015] More preferably, the precursor solution has a composition of 0.05–0.2 mol·L⁻¹. -1Anhydrous stannous chloride, antimony trichloride, 0.05–0.2 mol·L⁻¹ -1 Alkyl quaternary ammonium salt surfactants, 0.3–0.5 mol·L⁻¹ -1 Sodium hydroxide and deionized water; wherein the molar ratio of antimony trichloride to anhydrous stannous chloride is 0.05–0.2:1;
[0016] More preferably, the composition of the hydrothermal reaction precursor solution is 0.1–0.15 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride, 0.1–0.15 mol·L⁻¹ -1 Hexadecyltrimethylammonium bromide, 0.38–0.42 mol·L⁻¹ -1 Sodium hydroxide and deionized water, wherein the molar ratio of antimony trichloride to anhydrous stannous chloride is 0.08–0.15:1.
[0017] Furthermore, the method for preparing the precursor solution includes:
[0018] Tin salt and antimony salt are added to water, stirred, and then alkyl quaternary ammonium salt surfactant is slowly added while stirring continuously to obtain a mixed solution; alkaline solution is added dropwise to the mixed solution while stirring to obtain a precursor solution.
[0019] Furthermore, in step S3, the temperature of the hydrothermal reaction is 120–180°C, and the reaction time is 4–30 h. Preferably, the reaction temperature is 140–160°C, and the reaction time is 12–16 h.
[0020] Further, in step S4, the annealing temperature is 450-600℃ and the annealing time is 0.5-2h. Preferably, the annealing temperature is 500-550℃ and the annealing time is 1-1.5h. The annealing is preferably carried out in an air environment.
[0021] Furthermore, the negative electrode current collector is made of copper foil used in lithium-ion batteries.
[0022] A second aspect of the present invention provides a battery anode material of Sb-doped SnO2 prepared by the above method.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] (1) The present invention adds an appropriate amount of dopant Sb to SnO2 material, which can enhance the conductivity of the electrode. The ionic radii of Sn and Sb conform to the Hume-Rothery law, so the two metals can form a uniform solid solution.
[0025] (2) The hydrothermal reaction method of the present invention has the advantages of simple operation, high efficiency, environmental friendliness and low cost. The hydrothermal reaction can change the solubility of reactants, promote the occurrence of certain specific chemical reactions, and also facilitate the doping of Sb element into SnO2;
[0026] (3) This invention uses electrodeposition to prepare a SnO2-Sb interlayer on the current collector and uses it as a substrate in the hydrothermal reaction. It is generally believed that if a solid substrate is present during the hydrothermal reaction, when the local solute molecule concentration is high, nucleation will preferentially occur on the solid surface, i.e., "heterogeneous nucleation", which can reduce the energy barrier during crystal nucleation. In addition, the SnO2 crystal nuclei formed in the hydrothermal reaction are bonded to SnO2 on the substrate through chemical bonds, which is more robust and eliminates the need for binders, thereby improving the stability and mass energy density of the battery structure. This invention obtains the Sn-Sb interlayer directly on the surface of the current collector through electrodeposition. The presence of the interlayer reduces the interfacial resistance between the negative electrode material and the current collector.
[0027] (4) The present invention obtains an electrode with a surface of three-dimensional nanosheet structure SnO2-Sb. The three-dimensional nanosheet structure provides a large specific surface area, which can improve the wettability of the electrolyte to the electrode, thereby making more sufficient contact with the electrolyte, improving the electronic conductivity and lithium ion transport capability of the electrode, and playing a role in protecting the electrode interface during cycling.
[0028] (5) The alkyl quaternary ammonium salt surfactant used in this invention provides nitrogen doping sites for Sb-doped SnO2 anode materials, improves the lithium affinity of the anode materials, reduces the interface resistance, inhibits the growth of lithium dendrites, and improves battery life.
[0029] Other features and advantages of the present invention will be described in detail through the following specific embodiments. Attached Figure Description
[0030] Figure 1 This is a SEM image of the Sb-doped SnO2 lithium-ion battery anode material prepared in Example 1 of this invention;
[0031] Figure 2 This is a SEM image of the Sb-doped SnO2 lithium-ion battery anode material prepared in Comparative Example 2 of this invention.
[0032] Figure 3 This is a diagram showing the results of the electrode wettability test. Detailed Implementation
[0033] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0034] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0035] The raw materials and sources of the product are as follows:
[0036] Sodium pyrophosphate decahydrate (AR, Sinopharm Chemical Reagent Co., Ltd.), tartaric acid (AR, Merck Life Sciences), stannous chloride dihydrate (AR, Shanghai Titan Technology Co., Ltd.), antimony trichloride (AR, Shanghai Aladdin Biochemical Technology Co., Ltd.), gelatin (Tianjin Yuanli Chemical Co., Ltd.), anhydrous stannous chloride (AR, Shanghai Aladdin Biochemical Technology Co., Ltd.), cetyltrimethylammonium bromide (AR, Shanghai Titan Technology Co., Ltd.)
[0037] Other reagents or instruments used without a specified manufacturer are all commercially available products.
[0038] The first aspect of this invention provides a method for preparing an Sb-doped SnO2 battery anode material, comprising the following steps:
[0039] S1. Using the negative electrode current collector of the battery as the cathode, Sn-Sb intermediate layer is obtained by electrodeposition on the surface of the current collector.
[0040] S2. Heat-treat the current collector with the Sn-Sb intermediate layer on the surface to oxidize the Sn-Sb layer to SnO2-Sb;
[0041] S3. The current collector treated in step S2 is placed in a precursor solution containing an alkyl quaternary ammonium salt surfactant for hydrothermal reaction to obtain the electrode sheet.
[0042] S4. Anneal the electrode obtained in step S3 to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface.
[0043] Through the above technical solution, this invention uses an electrodeposition method to prepare a SnO2-Sb intermediate layer on the current collector, and then prepares a three-dimensional nanosheet structure SnO2-Sb with nitrogen-doped sites in situ through a hydrothermal reaction. This method has a simple preparation process, low production cost, reduces the use of binders, and improves the mass energy density of the battery. The SnO2 nanoparticles have good crystallinity and are uniformly loaded on the surface of the current collector, which can reduce the interfacial resistance between the negative electrode material and the current collector. The three-dimensional nanosheet structure increases the wettability of the electrode and the electrolyte, improves the performance of lithium-ion batteries, and also plays a role in protecting the electrode interface during cycling.
[0044] Preferably, the negative electrode current collector is made of copper foil used in lithium-ion batteries.
[0045] Preferably, the electrodeposition system in step S1 includes: using an inert electrode as the anode, and the components of the deposition solution include additives, tin salts, antimony salts, and solvents.
[0046] Preferably, the composition of the sediment fluid includes: 5–10 g·L⁻¹ -1 Tartaric acid, 100-120 g·L -1 Sodium pyrophosphate decahydrate, 20–40 g·L -1 Stannous chloride dihydrate, 3–6 g·L -1 Antimony trichloride, 0.5–1 g·L -1 Gelatin and deionized water, preferably, the composition of the sediment solution is 7-8 g / L. -1 Tartaric acid, 110-115 g·L -1 Sodium pyrophosphate decahydrate, 28–32 g·L -1 Stannous chloride dihydrate, 4-5 g·L -1 Antimony trichloride, 0.7–0.8 g·L -1 Gelatin and deionized water.
[0047] In one specific embodiment, the composition of the sedimentation solution is 7 g·L⁻¹. -1 Tartaric acid, 115 g·L -1 Sodium pyrophosphate decahydrate, 30 g·L -1 Stannous chloride dihydrate, 4.34 g·L -1 Antimony trichloride, 0.8 g·L -1 Gelatin and deionized water.
[0048] Preferably, the electrodeposition method in step S1 is direct current electrodeposition or pulsed electrodeposition, and the average current density is set to 10–30 mA·cm⁻¹. -2 The deposition time is 5–15 min; preferably, the average current density is 18–22 mA·cm⁻¹. -2 The deposition time is 8–12 minutes.
[0049] In a specific implementation, a stirrer, such as a magnetic stirrer, can be used to eliminate air bubbles adhering to the electrode surface during electrodeposition.
[0050] Preferably, the heat treatment temperature in step S2 is 450–550°C, and the holding time is 20–60 min. The heat treatment is preferably carried out in an air environment.
[0051] Preferably, the precursor solution in step S3 includes an alkyl quaternary ammonium salt surfactant, a tin salt, an antimony salt, an alkaline solution, and a solvent.
[0052] Preferably, the precursor solution has a composition of 0.05–0.2 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.05–0.2:1), 0.05–0.2 mol·L⁻¹ -1 Alkyl quaternary ammonium salt surfactants, 0.3–0.5 mol·L⁻¹ -1 Sodium hydroxide and deionized water; the alkyl quaternary ammonium salt surfactant is selected from one or more of hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide and dodecyldimethylammonium bromide, preferably hexadecyltrimethylammonium bromide (CTAB);
[0053] More preferably, the composition of the hydrothermal reaction precursor solution is 0.1–0.15 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.08–0.15:1), 0.1–0.15 mol·L⁻¹ -1 Hexadecyltrimethylammonium bromide (CTAB), 0.38–0.42 mol·L⁻¹ -1 Sodium hydroxide and deionized water.
[0054] In one specific embodiment, the hydrothermal reaction precursor solution has a composition of 0.1 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.1:1), 0.1 mol·L⁻¹ -1 Hexadecyltrimethylammonium bromide (CTAB), 0.4 mol·L -1 Sodium hydroxide and deionized water.
[0055] The inventors of this application discovered that when the concentration of alkyl quaternary ammonium salt cationic surfactants (such as CTAB) is low, their steric hindrance effect as stabilizers is insufficient to counteract van der Waals forces, i.e., intermolecular forces, leading to aggregation. Furthermore, excessive alkyl quaternary ammonium salt cationic surfactants are not conducive to the formation of the final three-dimensional layered structure; excess alkyl quaternary ammonium salt cationic surfactants may embed between SnO2-Sb nanosheets, hindering their self-assembly process. In addition, the antimony doping ratio is also a factor affecting the anode performance. A suitable Sb doping ratio (e.g., a molar ratio of antimony trichloride to anhydrous stannous chloride of 0.08–0.15:1) can improve the conductivity of the material, but as the doping ratio increases, excessive Sb may disrupt the SnO2 lattice structure, resulting in a significant increase in electrochemical impedance.
[0056] Furthermore, the method for preparing the precursor solution includes:
[0057] Tin salt and antimony salt are added to water, stirred, and then alkyl quaternary ammonium salt surfactant is slowly added while stirring continuously to obtain a mixed solution; alkaline solution is added dropwise to the mixed solution while stirring to obtain a precursor solution.
[0058] Furthermore, in step S3, the temperature of the hydrothermal reaction is 120–180°C, and the reaction time is 4–30 h. Preferably, the reaction temperature is 140–160°C, and the reaction time is 12–16 h.
[0059] Further, in step S4, the annealing temperature is 450-600℃ and the annealing time is 0.5-2h. Preferably, the annealing temperature is 500-550℃ and the annealing time is 1-1.5h. The annealing is preferably carried out in an air environment.
[0060] In this invention, when preparing three-dimensional nanosheet SnO2 using a hydrothermal method, Sn 2+ The oxidation process in aqueous solution can be described by the following reaction:
[0061] Sn 2+ +2H₂O→Sn(OH)₂↓+2H + (3-1)
[0062] Sn(OH)2→SnO+H2O (3-2)
[0063]
[0064]
[0065] When SnCl2 is added to deionized water, the solution quickly becomes cloudy. At this point, Sn... 2+ Rapid hydrolysis occurs, forming Sn(OH)₂ precipitate (Equation (3-1)). Subsequently, most of Sn(OH)₂ decomposes into stannous oxide (SnO) (Equation (3-2)), which is then oxidized to SnO₂ (Equation (3-3)); some Sn(OH)₂ is oxidized to Sn(OH)₄ precipitate (Equation (3-4)). When excess NaOH solution is added to the above mixture, the amphoteric compound Sn(OH)₄ reacts with OH⁻. - The reaction rapidly produces decomposable Sn(OH)6. 2- (Equation (3-5)), the substance decomposes into SnO2 nanocrystals under the high temperature and high pressure conditions of hydrothermal reaction (Equation (3-6)).
[0066] Sn(OH)₄ + 2OH⁻ - →Sn(OH)6 2- (3-5)
[0067] Sn(OH)6 2- →SnO2+2OH - +2H₂O (3-6)
[0068] Alkyl quaternary ammonium salt cationic surfactants play an important role in the formation of SnO2 nanosheets. When alkyl quaternary ammonium salt cationic surfactants are introduced into the above system, their cations react with Sn(OH)6. 2- Anions combine to form ion pairs through electrostatic interactions. The formation of these ion pairs allows alkyl quaternary ammonium salt surfactants to not only act as transport growth units (Sn(OH)6) 2- The surfactant acts as a medium, promoting the directional growth of SnO2 nanocrystals. On the other hand, the surfactant reduces the surface tension of the solution, lowering the energy required for new phase formation. During the hydrothermal reaction, the formed SnO2 nuclei spontaneously aggregate and grow in a direction that reduces surface energy. In this invention, the alkyl quaternary ammonium salt surfactant provides nitrogen doping sites for the Sb-doped SnO2 anode material, improving its lithium affinity, reducing interfacial resistance, inhibiting lithium dendrite growth, and improving battery life.
[0069] A second aspect of the present invention provides a battery anode material of Sb-doped SnO2 prepared by the above method.
[0070] The present invention will be further described below with reference to the embodiments:
[0071] Example 1
[0072] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material comprises the following steps:
[0073] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and a platinum electrode as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 7 g·L⁻¹. -1 Tartaric acid, 115 g·L -1 Sodium pyrophosphate decahydrate, 30 g·L -1 Stannous chloride dihydrate, 4.34 g·L -1 Antimony trichloride, 0.8 g·L -1 Gelatin and deionized water, with an average current density set at 20 mA·cm⁻¹ -2 The deposition time was 10 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0074] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 500℃ for 40 minutes.
[0075] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 160℃ for 12 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0076] Step S1: Add 0.1 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.1:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0077] Step S2: Slowly add 0.1 mol·L⁻¹ -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0078] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.4 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0079] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 550℃ for 1 hour to obtain an electrode with a surface of three-dimensional nanosheet structure SnO2-Sb.
[0080] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0081] Example 2
[0082] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material comprises the following steps:
[0083] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and graphite as the anode, pulse electrodeposition was performed in a deposition solution with a composition of 5 g·L⁻¹. -1 Tartaric acid, 100g·L -1 Sodium pyrophosphate decahydrate, 20 g·L -1 Stannous chloride dihydrate, 3 g·L -1 Antimony trichloride, 0.5 g·L -1 Gelatin and deionized water, with an average current density set at 10 mA·cm⁻¹ -2 The deposition time was 15 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0084] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 450°C for 60 minutes.
[0085] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 120℃ for 30 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0086] Step S1: Add 0.05 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.05:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0087] Step S2: Slowly add 0.05 mol·L -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0088] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.3 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0089] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 450°C for 2 hours to obtain an electrode with a surface of three-dimensional nanosheet structure SnO2-Sb.
[0090] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0091] Example 3
[0092] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material comprises the following steps:
[0093] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and platinum as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 10 g·L⁻¹. -1 Tartaric acid, 120 g·L -1 Sodium pyrophosphate decahydrate, 40 g·L -1 Stannous chloride dihydrate, 6 g·L -1 Antimony trichloride, 1 g·L -1 Gelatin and deionized water, with an average current density set at 30 mA·cm⁻¹ -2 The deposition time was 5 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0094] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 550°C for 20 minutes.
[0095] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 180℃ for 4 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0096] Step S1: Add 0.2 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.2:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0097] Step S2: Slowly add 0.2 mol·L⁻¹ -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0098] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.5 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0099] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 600℃ for 0.5h to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface.
[0100] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0101] Example 4
[0102] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material comprises the following steps:
[0103] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and platinum as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 10 g·L⁻¹. -1 Tartaric acid, 120 g·L -1 Sodium pyrophosphate decahydrate, 40 g·L -1 Stannous chloride dihydrate, 6 g·L -1 Antimony trichloride, 1 g·L -1 Gelatin and deionized water, with an average current density set at 30 mA·cm⁻¹ -2 The deposition time was 5 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0104] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 550°C for 20 minutes.
[0105] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 180℃ for 4 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0106] Step S1: Add 0.2 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.2:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0107] Step S2: Slowly add 0.5 mol·L -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0108] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.5 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0109] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 600℃ for 0.5h to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface.
[0110] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0111] Example 5
[0112] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material comprises the following steps:
[0113] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and platinum as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 10 g·L⁻¹. -1 Tartaric acid, 120 g·L -1 Sodium pyrophosphate decahydrate, 40 g·L -1 Stannous chloride dihydrate, 6 g·L -1 Antimony trichloride, 1 g·L -1 Gelatin and deionized water, with an average current density set at 30 mA·cm⁻¹ -2 The deposition time was 5 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0114] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 550°C for 20 minutes.
[0115] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 180℃ for 4 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0116] Step S1: Add 0.2 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.3:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0117] Step S2: Slowly add 0.2 mol·L⁻¹ -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0118] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.5 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0119] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 600℃ for 0.5h to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface.
[0120] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0121] Comparative Example 1
[0122] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material, compared with the example, does not involve electrodeposition of an intermediate layer, and the steps are as follows:
[0123] (1) Place the negative electrode current collector copper foil into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor volume), and maintain the temperature at 160℃ for 12 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0124] Step S1: Add 0.1 mol·L -1 Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.1:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0125] Step S2: Slowly add 0.1 mol·L⁻¹ -1 Add hexadecyltrimethylammonium bromide and continue stirring;
[0126] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.4 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0127] (2) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 550℃ for 1 hour to obtain an electrode with a surface of three-dimensional nanosheet structure SnO2-Sb.
[0128] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0129] Comparative Example 2
[0130] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material, compared with the example, does not add CATB to the precursor solution, and the steps are as follows:
[0131] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and a platinum electrode as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 7 g·L⁻¹. -1 Tartaric acid, 115 g·L -1 Sodium pyrophosphate decahydrate, 30 g·L -1 Stannous chloride dihydrate, 4.34 g·L -1 Antimony trichloride, 0.8 g·L -1 Gelatin and deionized water, with an average current density set at 20 mA·cm⁻¹ -2 The deposition time was 10 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0132] (2) Place the copper foil with the Sn-Sb intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 500℃ for 40 minutes.
[0133] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 160℃ for 12 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0134] Step S1: Add 0.1 mol·L -1Anhydrous stannous chloride and antimony trichloride (molar ratio of antimony trichloride to anhydrous stannous chloride is 0.1:1) were added to a certain amount of deionized water and stirred gently with a magnetic stirrer for 10 minutes.
[0135] Step S2: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.4 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0136] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 550°C for 1 hour to obtain the SnO2-Sb electrode.
[0137] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0138] Comparative Example 3
[0139] The method for in-situ preparation of Sb-doped SnO2 lithium-ion battery anode material, which does not contain Sb doping compared to the example, includes the following steps:
[0140] (1) Using copper foil, the negative electrode current collector of a lithium-ion battery, as the cathode and a platinum electrode as the anode, direct current electrodeposition was performed in a deposition solution with a composition of 7 g·L⁻¹. -1 Tartaric acid, 115 g·L -1 Sodium pyrophosphate decahydrate, 30 g·L -1 Stannous chloride dihydrate, 0.8 g·L -1 Gelatin and deionized water, with an average current density set at 20 mA·cm⁻¹ -2 The deposition time was 10 min, during which a magnetic stirrer was used to eliminate air bubbles attached to the electrode surface, and a Sn-Sb intermediate layer was prepared on the surface of the current collector.
[0141] (2) Place the copper foil with the Sn intermediate layer into a muffle furnace and perform high-temperature heat treatment in an air environment at a temperature of 500℃ for 40 minutes.
[0142] (3) Place the copper foil from step 2 into a hydrothermal reactor, add the precursor solution (the volume of which should not exceed 2 / 3 of the reactor's capacity), and maintain the temperature at 160℃ for 12 hours. After the reaction, rinse the electrode with anhydrous ethanol and deionized water. The preparation method of the hydrothermal reaction precursor solution is as follows:
[0143] Step S1: Add 0.1 mol·L -1 Anhydrous stannous chloride was added to a certain amount of deionized water and gently stirred for 10 minutes using a magnetic stirrer.
[0144] Step S2: Slowly add 0.1 mol·L⁻¹ -1Add hexadecyltrimethylammonium bromide and continue stirring;
[0145] Step S3: Add the separately prepared NaOH solution dropwise to the above solution until the final sodium hydroxide concentration is 0.4 mol·L⁻¹. -1 Stir for 30 minutes to prepare the precursor solution.
[0146] (4) The electrode after hydrothermal reaction is placed in a muffle furnace and annealed in an air environment at a temperature of 550°C for 1 hour to obtain an electrode with a surface of three-dimensional nanosheet structure SnO2.
[0147] The above-mentioned electrode sheets are used to make CR2032 coin cells, with lithium sheets as the counter electrode.
[0148] The CR2032 batteries obtained in Examples 1-5 and Comparative Examples 1-3 were left to stand for 6 hours, and then charge-discharge capacity tests and charge-discharge cycle tests were performed on the Xinwei charge-discharge test cabinet. The test temperature was 25±1℃. The test results are shown in Table 1.
[0149] First-cycle charge / discharge capacity and coulombic efficiency test: After standing for 3 hours, the device was activated by discharging at a small current of 0.1 mA for 5 hours, discharging at a current density of 39 mA / g, and charging at a current density of 78 mA / g. The cutoff voltage range was 0.005-2V. First-cycle coulombic efficiency = charging capacity / discharging capacity × 100%.
[0150] Charge-discharge cycle test: Discharge at a current density of 39 mA / g and charge at a current density of 78 mA / g, with a cutoff voltage range of 0.005-2V. The ratio of the charging capacity after 100 cycles to the first charging capacity is used as the capacity retention rate after 100 charge-discharge cycles.
[0151] The negative electrode sheets obtained in Examples 1-5 and Comparative Examples 1-3 were subjected to electrode wettability tests, and the test results are shown in Table 2.
[0152] Electrode wettability test: as attached Figure 3 As shown, the electrolyte (mainly dimethyl carbonate) was drawn into a capillary tube with an inner diameter of 0.2 mm, and the electrolyte height was 3 mm. Then, the capillary tube was vertically attached to different negative electrode plates, and the time for complete electrolyte wetting was observed.
[0153] Table 1
[0154]
[0155] Table 2
[0156]
[0157]
[0158] As can be seen from the results in Tables 1 and 2, the above-mentioned embodiments of the present invention achieve the following technical effects: The method for preparing Sb-doped SnO2 lithium-ion battery anode material provided by the present invention improves the conductivity of SnO2 anode material through Sb doping, and enables the anode material to be grown in situ on the anode current collector through hydrothermal reaction, reducing the use of binder and improving the mass energy density of the battery.
[0159] When CTAB is introduced, Sn(OH)6 2- Anions will react with CTA + (C 16 H 33 (CH3)3N + Cations combine through electrostatic interactions to form CTA. + -Sn(OH)6 2- Ion pairs. CTA + -Sn(OH)6 2- The formation of ion pairs allows CTAB to act not only as a transport growth unit Sn(OH)6 2- The medium CTAB also promotes the directional growth of SnO2 nanocrystals; on the other hand, as a surfactant, CTAB can reduce the surface tension of the solution and lower the energy required for the formation of new phases. During the hydrothermal reaction, the formed SnO2 crystal nuclei spontaneously aggregate and grow in a direction that reduces surface energy. In the embodiments of this invention, CTAB provides nitrogen doping sites for the Sb-doped SnO2 anode material, improving the lithium affinity of the anode material, reducing interfacial resistance, inhibiting the growth of lithium dendrites, and improving battery life. The three-dimensional nanosheet structure provides a large specific surface area, which can improve the wettability of the electrolyte to the electrode, thereby ensuring more sufficient contact with the electrolyte and improving the electronic conductivity and lithium-ion transport capacity of the electrode.
[0160] In Example 4, 0.5 mol·L⁻¹ was added. -1 The high concentration of hexadecyltrimethylammonium bromide reduces the electrochemical performance and electrolyte wettability of the electrodes as shown in Table 1-2.
[0161] In Example 5, the molar ratio of antimony trichloride to anhydrous stannous chloride was 0.3:1. Due to the excessively high Sb doping ratio, the impedance of the electrode increased, resulting in a decrease in the electrochemical performance shown in Table 1.
[0162] from Figure 1 and Figure 2 It can be seen that when CTAB is not added ( Figure 2The current collector surface does not have a three-dimensional layered structure, and a large number of exposed intermediate layers can be observed. The surface has only a small number of SnO2-Sb nanoparticles and clusters of similar nanosheet structures. Therefore, the addition of CTAB not only improves the electrochemical performance of the electrode, but also has a certain impact on the formation of the three-dimensional nanosheet structure.
[0163] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are within the spirit and scope of the present invention.
Claims
1. A method for preparing an Sb-doped SnO2 battery anode material, characterized in that, Includes the following steps: S1. Using the negative electrode current collector of the battery as the cathode, Sn-Sb intermediate layer is obtained by electrodeposition on the surface of the current collector. S2. Heat-treat the current collector with the Sn-Sb intermediate layer on the surface to oxidize the Sn-Sb layer to SnO2-Sb; S3. The current collector treated in step S2 is placed in a precursor solution containing an alkyl quaternary ammonium salt surfactant for hydrothermal reaction to obtain the electrode. S4. Anneal the electrode obtained in step S3 to obtain an electrode with a three-dimensional nanosheet structure SnO2-Sb on the surface. The electrodeposition system in step S1 includes: using an inert electrode as the anode, and the components of the deposition solution include additives, tin salts, antimony salts and solvents, wherein the additives include one or more of tartaric acid, sodium pyrophosphate decahydrate and gelatin. The precursor solution in step S3 includes an alkyl quaternary ammonium salt surfactant, a tin salt, an antimony salt, an alkaline solution, and a solvent; the alkyl quaternary ammonium salt surfactant is selected from one or more of hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, and dodecyldimethylammonium bromide.
2. The preparation method according to claim 1, characterized in that, In the electrodeposition system of step S1: the tin salt is stannous chloride dihydrate, the antimony salt is antimony trichloride, and the solvent is water; The components of the sediment include: 5~10 g•L -1 Tartaric acid, 100~120g•L -1 Sodium pyrophosphate decahydrate, 20~40 g•L -1 Stannous chloride dihydrate, 3~6 g•L -1 Antimony trichloride, 0.5~1 g•L -1 Gelatin and water.
3. The preparation method according to claim 2, characterized in that, The composition of the sediment is 7~8 g•L -1 Tartaric acid, 110~115 g•L -1 Sodium pyrophosphate decahydrate, 28~32 g•L -1 Stannous chloride dihydrate, 4~5 g•L -1 Antimony trichloride, 0.7~0.8 g•L -1 Gelatin and water.
4. The preparation method according to claim 1 or 2, characterized in that, In step S1, the electrodeposition method is either direct current electrodeposition or pulsed electrodeposition, and the average current density is set to 10~30 mA·cm⁻¹. -2 The deposition time is 5-15 minutes.
5. The preparation method according to claim 4, characterized in that, The average current density of electrodeposition in step S1 is 18~22 mA·cm⁻¹ -2 The deposition time is 8-12 minutes.
6. The preparation method according to claim 1, characterized in that, In step S2, the heat treatment temperature is 450~550℃, the holding time is 20~60min, and the heat treatment is carried out in an air environment.
7. The preparation method according to claim 1, characterized in that, In the precursor solution of step S3, the alkyl quaternary ammonium salt surfactant is hexadecyltrimethylammonium bromide, the tin salt is anhydrous stannous chloride, the antimony salt is antimony trichloride, and the alkaline solution is sodium hydroxide or potassium hydroxide.
8. The preparation method according to claim 7, characterized in that, The precursor solution has a composition of 0.05~0.2 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride, 0.05~0.2 mol·L⁻¹ -1 Alkyl quaternary ammonium salt surfactants, 0.3~0.5 mol·L -1 Sodium hydroxide and deionized water; wherein the molar ratio of antimony trichloride to anhydrous stannous chloride is 0.05~0.2:
1.
9. The preparation method according to claim 8, characterized in that, The composition of the hydrothermal reaction precursor solution is 0.1~0.15 mol·L⁻¹. -1 Anhydrous stannous chloride, antimony trichloride, 0.1~0.15 mol·L -1 Hexadecyltrimethylammonium bromide, 0.38~0.42 mol·L -1 Sodium hydroxide and deionized water, wherein the molar ratio of antimony trichloride to anhydrous stannous chloride is 0.08~0.15:
1.
10. The preparation method according to claim 1, characterized in that, The method for preparing the precursor solution includes: Tin salt and antimony salt are added to water, stirred, and then alkyl quaternary ammonium salt surfactant is slowly added while stirring continuously to obtain a mixed solution; alkaline solution is added dropwise to the mixed solution while stirring to obtain a precursor solution.
11. The preparation method according to claim 1, characterized in that, The hydrothermal reaction temperature in step S3 is 120~180℃, and the reaction time is 4~30h.
12. The preparation method according to claim 11, characterized in that, In step S3, the hydrothermal reaction temperature is 140~160℃ and the reaction time is 12~16h.
13. The preparation method according to claim 1, characterized in that, In step S4, the annealing temperature is 450~600℃ and the annealing time is 0.5~2h.
14. The preparation method according to claim 13, characterized in that, In step S4, the annealing temperature is 500~550℃ and the annealing time is 1~1.5h; the annealing is carried out in an air environment.
15. The preparation method according to claim 1, characterized in that, The negative electrode current collector uses copper foil used in lithium-ion batteries.
16. A battery anode material of Sb-doped SnO2 prepared by the method of any one of claims 1-15.
Citation Information
Patent Citations
Antimony negative electrode and aqueous alkaline battery based on antimony negative electrode
CN114709357A
Electrode material for synthesizing dialdehyde starch by electrolyzing starch, preparation method of electrode material and electrochemical preparation method of dialdehyde starch
CN114807988A
